Demographic and health predictors of telomere length during adolescence. Issue 7 (16th July 2022) - Kertes, Darlene A.; Leri, John; Duan, Ke; Tarrence, Jake; Browning, Christopher; Pickler, Rita; Ford, Jodi
Abstract: Telomere length (TL) is proposed to play a mechanistic role in how the exposome affects health outcomes. Little is known about TL during adolescence, a developmental period during which precursors of adult‐onset health problems often emerge. We examined health and demographic sources of variation in TL in 899 youth aged 11–17. Demographic and health information included age, sex, race, household income, caregiver age and marital status, youth tobacco exposure, body mass index, pubertal status, health problems, medication use, and season of data collection. Genomic DNA was extracted from saliva, and T/S ratios were computed following qPCR. Age, race, season of data collection, and household income were associated with the telomere to single copy (T/S) ratio. We found that T/S ratios were larger at younger ages, among Black youth, for saliva collected during autumn and winter, and among households with higher income. Analyses stratified by race revealed that the association between age and T/S ratio was present for Black youth, that season of collection was present across races, but that family demographic associations with T/S ratio varied by race. The results provide information for future telomere research and highlight adolescence as a potentially important developmental phase for racial disparities in telomere shortening and health.